Effect of drying conditions on physiological quality of cowpea seeds of the cultivar brs-tumucumaque - Assis, Miquéias de Oliveira (2023)
Seed drying has many advantages, but it can cause irreversible damages, compromising the physiological quality of seeds, especially when they present high water contents. The objective of this work was to evaluate the effect of drying conditions (inside and outside the pod) on the physiological quality of cowpea seeds of the cultivar BRS-Tumucumaque before and after storage. A completely randomized experimental design with four replications was used, in a split-plot arrangement. The plots consisted of combinations of harvest seasons (1, 2, 3, 4, and 5) and artificial seed drying conditions (inside and outside the pod); and the subplots consisted of storage times (0 and 6 months). The seed water contents were determined and the seeds were evaluated for germination, first germination count, emergence, emergence index, accelerated aging, and electrical conductivity. Higher physiological quality was found for dried seeds inside the pods, which was more evident in seasons 1 and 2, in both storage times. In the other seasons, the drying conditions had no effect on seed germination and vigor at the beginning of storage. The dried seeds inside the pods showed greater vigor after six months of storage. Drying seeds inside the pods favors the maintenance of physiological quality and allows artificial drying of cowpea seeds of the cultivar BRS-Tumucumaque with water content of 47%. Artificial drying of seeds with water contents higher than 32.5% is not recommended for the condition outside the pod. The seed physiological potential decreases after six months of storage, regardless of the drying condition.